2008
DOI: 10.1097/ccm.0b013e318186a3e7
|View full text |Cite
|
Sign up to set email alerts
|

Understanding posttraumatic stress disorder-related symptoms after critical care: The early illness amnesia hypothesis*

Abstract: Amnesia for the early period of critical illness (early amnesia) was positively associated with the level of posttraumatic stress disorder-related symptoms, which may be a proxy for severity of disease at the time of intensive care unit admission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
0
14

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(107 citation statements)
references
References 15 publications
2
91
0
14
Order By: Relevance
“…The Memory Tool cannot be added in order to obtain an overall score, while the individual items developed to evaluate types of memories (delusional, affective, factual) are also not interconnected, therefore they cannot be considered parts of the same domain. In the present study, we used the version translated from English into Portu-guese by Granja et al (2008).…”
Section: Participantsmentioning
confidence: 99%
“…The Memory Tool cannot be added in order to obtain an overall score, while the individual items developed to evaluate types of memories (delusional, affective, factual) are also not interconnected, therefore they cannot be considered parts of the same domain. In the present study, we used the version translated from English into Portu-guese by Granja et al (2008).…”
Section: Participantsmentioning
confidence: 99%
“…3 Penilaian nyeri diperoleh dari laporan pasien sendiri merupakan "gold standard" dalam menilai intensitas nyeri, pasien biasanya akan memberitahu ketika merasakan nyeri, dan begitu juga apabila pasien tersebut tidak merasakan nyeri. 4 Nyeri merupakan salah satu gejala yang paling umum pada pasien sakit kritis dan dialami oleh setiap pasien dalam cara yang unik. Hal demikian tidak berarti pasien yang tidak dapat berkomunikasi atau dengan penggunaan ventilasi mekanik tidak dapat dilakukan penilaian nyeri, ekspresi wajah, gerakan tangan atau indikator perilaku lainnya dapat dijadikan sarana komunikasi untuk mengungkapkan rasa nyeri.…”
Section: 2unclassified
“…ICU-related delusional memories are estimated to be present in around 30% to 70% of patients [10,12,13], are often persecutory in nature, and tend to be recalled with high vividness and in substantial detail [2].The direct cause of these delusional memories is unknown but is thought to be related to a combination of medication (including adrenaline, corticosteroids, opiates and sedative drugs such as propofol and benzodiazepine), sleep deprivation, and critical illness [12]. The literature surrounding the relationship between recall of absent, traumatic or delusional memories and psychological disorders is mixed, with different authors finding positive [10,12,14,15] and negative associations [7,16]. The association between delusional memories and the psychological distress of ICU survivors has been mainly attributed to the strong vividness with long duration and high emotional content of these memories when compared with memories of real events [13].…”
Section: Recovery From Critical Illnessmentioning
confidence: 99%
“…The aim of patient diaries is to provide ICU survivors with an accurate and informative collection of events, improving the memory recall of factual information. Delusional memories have been associated with anxiety, depression, post-traumatic stress symptomatology [9,12] and poor health-related quality of life [16].The aim of a diary is to provide a coherent narrative of the illness period, clarifying gaps in memory and diminishing the impact or dominance of imagined occurrences and hallucinations [18]. It has also been suggested that diaries can be used by relatives to encourage the healing process, after their own vicarious traumatic experience or as a basis for discussion about the patient's illness experience [10].…”
Section: Icu Diaries To Improve Recovery From Critical Illnessmentioning
confidence: 99%